Baixo peso ao nascer e sua relação com as más oclusões na dentição decídua: coorte brisa - SILVA JÚNIOR, Antônio Carlos (2018)
Malocclusions are disorders in dental position resulting by skeletal development problems in the facial bones or dentoalveolar disharmony. Take a third place in the prevalence scale of dental diseases, been object of great epidemiologic interesting, both by etiology and preventive or control cares. The influence of perinatal factors in your etiology, like low birth weigth(LBW), still not been informed. LBW (above 2.500g) can be expressed by consequence of preterm birth (PTB) and intrauterine growth restriction (IUGR), conditions that involves a series by disturbs in general growth, facials structures and morphologic and size of teeth. Furthermore, during perinatal and postnatal period, these children are more subject to breath problems, reduction in breastfeeding and early non-nutritives habits. The aim of this study is analize the relationship between LBW and kinds of malocclusion that cause more functional and aesthetic impact in primary dentition (overjet, anterior and posterior crossbite and crowding), considering effects of growth, breathing, breastfeeding and pacifiers sucking like possible mediators in these relationship. It is a retrospective cohort with a subsample of cohort birth BRISA, totalizing 217 children that was submitted to orthodontics evaluation 24-36 months after birth. Statistical descriptive analysis data was taken by means of absolute frequency, percentage, means and standart deviation. To the numeric variables, distributing of normality was measured by Shapiro-Wilk test, coefficients tests of asymmetry and curtose. Test t-student and Anova followed by Post Hoc Tukey were utilized to the parametric data and tests of Mann-Whitney and Kruskal-Wallis to the non-parametrics. Categorical variables were summarized by frequency and analised by Qui-quadrado and Fischer Exact tests. It was carried out structural equation modeling using MPlus 7.0 software to check hypothesis of LBW has a direct effect in malocclusion, mainly mediated by action from indicators of growth (way 1), breath disturbs (way 2) and by time of breastfeeding and use of pacifiers (way 3). Outcomes found that there is no direct effect between LBW and development of overjet (CFP = -1.536, p = 0.275), anterior crossbite (CFP = -0.593; p = 0.054), posterior crossbite (CFP = 0581, p = 0,660) and crowding (CFP = 4.449, p = 0.409). Therefore, this study is justified by research shortage and divergence in literature about LBW and your two components (PTB and IURG) like potentials risk factors to malocclusion. Thus, we gathered this three indicators in a only latent variable (LBW) as exposition and we tested four models with differents outcomes (ACB, PCB, overjet and crowding), passing for direct and indirects ways, mediaded by latents variables growth and breathing and by observed latents breastfeeding time and pacifiers use.